Seed production and quality in grafted cucumber - Toledo Rodrigues Claudio, Marina De; Gomes Nakada-Freitas, Pâmela [UNESP]; Barbosa Tavares, Ana Emília; Oliveira Magro, Felipe; Ismael Inácio Cardoso, Antonio [UNESP] (Taylor & Francis, 2020)
Grafting helps manage soil pathogens, and can improve vigor, humidity tolerance, cold and heat resistance, tolerance to soil salinity and alkalinity, and increase production and fruit quality in cucumber (Cucumis sativus L.). There are no studies about how grafting affects production and quality of seed in cucumber. The objective was to evaluate the influence of rootstocks on cucumber grafted on production and seed quality in the open field. Treatments were: ungrafted plants, and cucumber grafted on commercial pumpkin (Cucurbita moschata D.) rootstocks “Shelper,” “Exccite Ikky,” “Keeper,” and “Tropical.” Longer (35.0 cm) and heavier fruit (534 g per fruit), and higher seed production per fruit (3.82 g) were obtained in plants grafted on “Keeper” rootstock and ungrafted plants. There was no difference between ungrafted and grafted plants for weight of 1000 seed (average of 26.6 g), first count of standard germination test (avg. 97.1%) and germination (avg. 99.6%). The best rootstock was “Keeper,” resulting in heavier fruit and higher seed production per fruit, without affecting seed quality. No grafted treatment was superior to ungrafted plants regarding seed yield and quality. It does not appear to be advantageous to use grafting due to lack of direct benefit and because of extra cost.
Keywords: Cucumis sativus; Cucurbita; germination; grafting; rootstock